Morphological tricks and blessed genitalia: rectifying the family placement of Fijicolana tuberculata (Opiliones: Laniatores: Zalmoxidae) - Pérez-González, Abel; Sharma, Prashant P.; Proud, Daniel N. (Zootaxa, 2016)
The type specimens of Fijicolana tuberculata Roewer, 1963 were re-examined and the male genital morphology is illustrated and described for the first time. Despite the presence of several morphological features that are typical of Samoidae, such as the presence of scopulae on legs III and IV, genital morphology unambiguously indicates that this species belongs to the Zalmoxidae rather than to the Samoidae. Fijicolana Roewer, 1963 is newly synonymized with Zalmoxis Sørensen, 1886. However, the newly implied combination is preoccupied by Z. tuberculatus Goodnight & Goodnight, 1948 thus the replacement name Zalmoxis roeweri nom. nov. is proposed to avoid secondary homonymy. The definition of Z. roeweri nom. nov. is amended, and the morphology of this species is compared with other representatives of Zalmoxidae and Samoidae. We conclude that the presence of scopulae alone is not a sufficiently diagnostic characteristic for Samoidae and, therefore, correctly placing taxa into families within Samooidea + Zalmoxoidea requires additional morphological evidence (e.g. genital morphology). In light of this result, we point out that the "scopulated" Australasian samoids Badessania metatarsalis Roewer, 1949, Sawaiellus berlandi Roewer, 1949 and Parasamoa gressitti Goodnight & Goodnight, 1957 require re-examination in order to detect potential errors in their family placement.